2015
DOI: 10.1007/s13197-015-1858-4
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of tannase from cashew testa using Aspergillus niger MTCC5889 by solid state fermentation

Abstract: The use of better carbon sources and efficient production strains were deemed as promising strategies to economize tannase production. A novel agro-residue, cashew testa, was tested for the production of tannase under solid-state fermentation (SSF) using Aspergillus niger CEPC 11. CEPC 11 was identified by 18S rDNA typing as Aspergillus niger and deposited in International depositing Authority under MTCC number 5898 and NCBI accession number KM516789. The enzyme was purified 11 fold to obtain tannase with a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Figure 4 explains the process of electrophoresis in polyacrylamide gel with SDS for standard proteins and pure enzyme, the results were different between researchers, it agreed with the findings of [20] that the molecular weight for tannase product from Aspergillus niger reached to 89.9 KDa estimated in an SDS-PAGE, while molecular weight was 80 KDa for tannase product from Aspergillus niger in SDS-PAGE [16].…”
Section: Molecular Weightsupporting
confidence: 62%
“…Figure 4 explains the process of electrophoresis in polyacrylamide gel with SDS for standard proteins and pure enzyme, the results were different between researchers, it agreed with the findings of [20] that the molecular weight for tannase product from Aspergillus niger reached to 89.9 KDa estimated in an SDS-PAGE, while molecular weight was 80 KDa for tannase product from Aspergillus niger in SDS-PAGE [16].…”
Section: Molecular Weightsupporting
confidence: 62%
“…When the enzyme was placed under temperatures above 40°C, a decrease in tannase activity was observed. Some tannase characterisation studies using genus Aspergillus have indicated that A. niger MTCC5889 under SSF and using cashew bagasse as a substrate yielded optimum temperature and pH level for tannase production at 40°C and 5.5, respectively (Viswanath et al, 2015). Similarly, using A. niger, Ni et al (2015) demonstrated maximum tannase activity at a pH level of 5.5 and with an optimum temperature at 50°C.…”
Section: Resultsmentioning
confidence: 99%
“…2b) showed the enzyme to be 66.5 kDa. Aspergillus niger MTCC5889 tannase analysed by SDS-PAGE had an 89.9 kDa molecular weight (Viswanath et al, 2015). The recombinant (rAoTanA) and native (AoTanA) enzymes produced by Aspergillus oryzae and expressed by Pichia pastoris yielded molecular weights of 45-80 and 45-75 kDa, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the previous studies have used the yield or activity of the target product as the sole index to evaluate or optimize SSF systems, such as those used for l (+)-lactic acid production from sugarcane bagasse [ 27 ], ethanol production from rice straw and husk [ 28 ], and rapeseed peptide production from rapeseed meal [ 29 ]. The same problem of complicated microbial biomass determination is also encountered in tannase SSF, because high amounts of agricultural byproducts, for example, castor bean residues [ 12 ], cashew testa [ 30 ], coffee husk [ 31 ], and tea stalk [ 26 ], are used as solid media to produce tannase. The previous studies have optimized fermentation conditions on the basis of a single evaluation index, including tannase activity, and ignored the effect of cell growth on tannase synthesis.…”
Section: Discussionmentioning
confidence: 99%